Dari Makna ke Tujuan: Relevansi Maqasid al-Qur’an dalam Dinamika Studi Tafsir Kontemporer - Muttaqin, Imam (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to examine the fundamental concepts, origins, and significance of Maqasid al-Qur’an in the interpretation of Qur’anic verses. Maqasid al-Qur’an refers to the endeavor of uncovering the divine objectives and purposes underlying the Qur’anic text, which essentially guide humanity toward a better life in accordance with the principles established by Allah SWT. Methodologically, this research employs a qualitative approach through library research, emphasizing descriptive analysis of both classical and contemporary literature in Qur’anic exegesis and ‘ulūm al-Qur’an. The findings indicate that the concept of Maqasid al-Qur’an has been discussed by numerous scholars within various works of tafsir and Qur’anic studies, generally categorized into two types: maqasid ‘ammah (general objectives) and maqasid khassah (specific objectives). Furthermore, maqasid can be identified within the linguistic structure of the Qur’an—ranging from chapters and words to letters—each containing profound semantic and rhetorical dimensions. These findings affirm that the application of Maqasid al-Qur’an in interpretation not only enriches exegetical methodology but also reinforces the Qur’an’s role as a universal guide for human life. Theoretically, this research contributes to strengthening the paradigm of tafsir maqāṣidī—an interpretative approach that positions divine objectives and values as the epistemological foundation in understanding the Qur’an. This approach offers the potential to integrate textual and contextual dimensions in Qur’anic studies, thereby enhancing the relevance of tafsir in addressing contemporary intellectual and humanitarian challenges.